A further account of the province of Pennsylvania and its improvements : for the satisfaction of those that are adventurers, and enclined to be so - Penn, William, 1644-1718 ([publisher not identified], 1685)
1685 London publication of William Penn's further account of the Province of Pennsylvania and its improvements, printed to encourage emigration to that colony. Included were information that ninety ships sailed to Pennsylvania since 1682, with approximately 7,200 persons arriving in the colony; descriptions of Philadelphia; and information regarding produce from the earth and water.